Die Krise der Ordnungspolitik als Kommunikationskrise - Bernhard Seliger; Ralph M. Wrobel (OrdnungsPolitisches Portal (OPO), 2007)
The conception of economic order policy (in German: Ordnungspolitik) has been the theoretical foundation of the Social Market Economy in Germany after World War II. But nowadays, the conception of Ordnungspolitik is in a fundamental crisis. It has been removed by Keynesian conceptions or still an arbitrariness of economic policy. Currently, while in Germany growth rates increase there is taken less and less notice of the necessity of fundamental changes in economic policy. In contrast, the current crisis of economic order policy is surprising. The collapse of central planned economies in Eastern Europe as well as the crisis of developing countries in Southeast Asia has allowed market ideas to appear as a clear winner in the competition of economic ideas. Many former transformation countries in central and Eastern Europe are nowadays rising dynamic market economies. Other countries of the world have already successfully reformed their overloaded welfare states, with only Germany seeming to face insurmountable obstacles. The current crisis of order policy is also of communication. In the end the discussion on order policy as main economic policy has been replaced by the contraposition of neo-liberal and globalization-critical conceptions. However, the crisis of order policy is at least partly also a crisis of communicating order policy positions. This fact refers both to the science, where regulatory-political teachings and research were consistently pushed back without resistance, and also to the policy, where basic principles of economic order policy became nearly insignificant. It is however the inability of German politicians and scientist to make clear economic order policy which keeps Germany imprisoned in its stagnation. To improve the position of the conception of economic order policy - or in other words of Social Market Economy - the authors demand a better manifestation of these conceptions via internet. As a first step they created the Ordnungspolitisches Portal.
Keywords: 330; Economic Order Policy; Social Market Economy; Germany